Stress Management Training Effects on Mental Health of Intellectual Disabilities Children Parents - Kalashloo, Mahboobe; Rafeie, Shahram; Baghshomali, Somayeh; Aligholizadeh Moghadam, Sahar; Naeim, Mahdi (Opción, 2019)
The purpose of this study is to investigate the effect of education on mental health and the effect of education on stress levels. This research is a kind of similar test with a control group with pretext and pasttext and follow up text. Statistical society, including all mental retorted children's parents of exclusive elementary schools and social welfare of Ardabil. Education will make mothers better off their mental retardation, identify their strengths and weaknesses, and ultimately expose themselves to increasing weaknesses and creating positive points. As a result, you can accept the facts better and reduce the stress.